THE EFFICIENCY OF SYMBIOTIC NITROGEN FIXATION IN AGROCENOSES OF SOYBEAN VARIETIES AT DIFFERENT LEVELS OF MINERAL NUTRITION - Чинчик, О. С. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The agricultural means aimed at creating of favorable conditions for the symbiotic system in soybean plants and improving the efficiency of symbiotic nitrogen fixation are suggested in the article. The research is based on weight; measurement and calculation methods to determine the number; nodules wet weight and indicators of active symbiotic potential and the number of symbiotically fixed nitrogen in soybean agrocenoses. As a result of the research it was founded that the best conditions for the formation of nodules on the roots of soybean plants are provided by fertilizer Wuxal. Among the studied varieties; the maximum number of nodules was formed by Khutorianochka soybean variety. But Khutorianochka soybean variety according to the wet weight of nodules yielded such varieties as Femida; Omeha vinnyts’ka and Monada. The biggest mass of active nodules in the experiment was during sowing of such soybean varieties as Femida using Wuxal fertilizers. It was established that the efficiency of symbiotic nitrogen fixation was more influenced by soybean varietal characteristics. Among the varieties the highest rates of active symbiotic potential and the number of symbiotically fixed nitrogen for all versions of Femida soybean varieties were designed. Among the investigated fertilizers the use of Wuxal was more effective in comparison to Avatar-1. Thus; under the conditions of western steppes better circs for the formation of symbiotic soybean plants were provided by Wuxal fertilizer. Among the varieties studied; the maximum amount of symbiotic nitrogen was fixed by Femida soybean variety.